Insights into Chinese Canadian culture: enablers and barriers for fruit and vegetable intake - Gill, Simran; Lam, Debbie; Choy, Natalie; Swann, Anne; Liow, Eric; Tang, Tricia S. (Frontiers in Public Health, 2024)
Background: Fruits and vegetables (F&V) play a vital role in promoting health and preventing diseases. Numerous studies have demonstrated the association between F&V consumption and reduced risks of cardiovascular disease, cancer, and mortality. Despite the high priority of public health in promoting F&V intake, Chinese immigrants in Canada often fall below national guidelines in their consumption. Understanding the factors influencing F&V intake in this community is crucial for developing effective interventions.Methods: This study used an applied ethnographic research approach to explore gain insight into the enablers and barriers that influence the determinants of F&V intake among Chinese-Canadian adults in Richmond, BC. Semi-structured interviews and '"pPhotovoice'" group sessions were conducted to gather qualitative data from community participants and health care providers (HCPs).Results: The research identified four key themes: (1) Cultural differences around how vegetables are perceived, consumed and prepared; (2) Motivators and strategies for increasing vegetable and fruit intake; (3) Lack of culturally relevant dietary education and resources; and (4) Importance of value in vegetable/fruit-related decisions. Participants showed a strong preference for the traditional Eastern diet, with cost of food and lack of knowledge about Western vegetables acting as barriers to dietary diversity. The study also highlighted the need for culturally tailored educational resources to effectively promote F&V consumption.Conclusions: By adopting a multi-modal approach, incorporating both interviews and "pPhotovoice" sessions, this research provided comprehensive insights into the participants' perspectives and experiences related to F&V intake. Understanding these factors can guide the development of culturally appropriate interventions to increase F&V consumption among Chinese-Canadian adults in Richmond, BC, and potentially improve their overall health and well-being. Future studies should consider the heterogeneity within the Chinese immigrant population and target a more balanced representation of age groups to further enhance our understanding of F&V intake patterns in this community.